2019
DOI: 10.1108/er-09-2018-0245
|View full text |Cite
|
Sign up to set email alerts
|

Family friendly policies and the Omani Labour Law

Abstract: Purpose The purpose of this paper is to take cognisance of the work–life balance (WLB) challenges facing working women in Oman, make a review of the family-friendly policies (FFPs), related provisions in labour laws of various nations, and identify and suggest some FFP-based solutions for attracting women to private sector jobs. Design/methodology/approach Initially, desk research was used to review the labour laws of the six Gulf Cooperation Council (GCC) countries and some pioneering countries known for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Allen, Herst, Bruck & Sutton (2000) have found that the problems associated with WLB can affect QWL adversely. Belwal & Belwal (2014) have identified WLB to be a significant predictor of QWL. Sojka ( 2014) developed an empirical relationship in which WLB was associated with QWL and job satisfaction and type of employment contract constituted the other two dimensions.…”
Section: Relationship Between Work-life Balance and Qwlmentioning
confidence: 99%
“…Allen, Herst, Bruck & Sutton (2000) have found that the problems associated with WLB can affect QWL adversely. Belwal & Belwal (2014) have identified WLB to be a significant predictor of QWL. Sojka ( 2014) developed an empirical relationship in which WLB was associated with QWL and job satisfaction and type of employment contract constituted the other two dimensions.…”
Section: Relationship Between Work-life Balance and Qwlmentioning
confidence: 99%
“…But, notably, the increase in the number of women in the workforce was not followed by an increase in the count of men working in the domestic and family spheres, which still forces women to do household chores additionally. The gender-based work roles performed by women in today's industrialized economies are the clearest reflection of the reality of the female working population (Belwal et al, 2020;Rincon and Martinez, 2020). Women in both professional and non-professionals work roles do housework, and they rarely have free or leisure time for themselves.…”
Section: Gender Discrepancymentioning
confidence: 99%
“…The major factors impeding the progression and advancement of women employees in organizations include the stress to prioritize multiple tasks, the lack of FWA, the absence of career opportunities and manifold family commitments. Care obligations, such as sharing roles and responsibilities with a spouse in a dual-earner family or providing care to elderly parents, tend to have a significant impact on women's career choices (Belwal et al, 2020;Ren and Caudle, 2020). The factors responsible for bringing changes in their career choices and decision to "opt-out" or remain in the workforce had received very little attention in the extant literature (Lim and Rasdi, 2019).…”
Section: Gender Discrepancymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of working women, as example in Oman, play a big part of the skilled human resources inventory. Nevertheless, those working women in the private sector need flexible working hours, privacy at work and reduced work hours (Belwal, Belwal, & Al-Hashemi, 2020). Study in Brazil showed access to maternity and paternity leave was inequal from the perspective of social stratification of gender, class, race and age (Sorj & Fraga, 2020).…”
Section: Introductionmentioning
confidence: 99%